Chitooligosaccharide enhanced the efficacy of Bacillus amyloliquefaciens CAS02 for the control of tobacco black shank - Zeng, Xiangnan; Zhang, Xin; Peng, Bo; Xie, Bingyue; Yuan, Yuan; Yao, Hui; You, Xiangwei; Wei, Jianyu; Li, Yiqiang (Frontiers in Microbiology, 2023)
Tobacco black shank is a devastating soil-borne disease caused by the oomycete Phytophthora nicotianae (P. nicotianae), severely hamper tobacco production worldwide. However, the synergistic effect of biocontrol bacteria and marine polysaccharides/oligosaccharides on tobacco black shank control was few documented. In this study, Bacillus amyloliquefaciens CAS02 (CAS02) and chitooligosaccharide (COS) were screened firstly, and their synergistic antagonistic effect against P. nicotianae and the underlying mechanism were investigated in vitro and in vivo. In vitro experiments showed that, compared with the application of CAS02 or COS alone, co-application of CAS02 and COS significantly increased the inhibition rate against P. nicotianae by 11.67% and 63.31%, respectively. Furthermore, co-application of CAS02 and COS disrupted the structure of mycelia to a greater extent. The co-application of CAS02 and COS showed synergistic effect, with the relative control effect maintained above 60% during the 60-day pot experiment, significantly higher than that of application CAS02 or COS alone. The combined application of CAS02 and COS reduced the relative abundance of P. nicotianae in the rhizosphere soil and increased the relative abundance of bacterial taxa potentially involved in disease suppression, such as Nocardioides, Devosia and Bradyrhizobium. Meanwhile, CAS02 and COS synergistically activated salicylic acid (SA), ethylene (ET), and hypersensitive response (HR) defense signaling pathways in tobacco plants. Our findings demonstrate that co-application of CAS02 and COS remarkably improve the relative control effect against tobacco black shank through multiple pathways and provide a promising strategy for the efficient green control of tobacco black shank.